Chinese Opera in America (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This essay presents a panorama of Chinese operas in the United States of America. From a historical perspective, it highlights the first traditional productions in 19th-century California by immigrants from Guangdong, and discusses the development and expansion of the genre to the New York stages throughout the following centuries.
Keywords: Chinese traditional theatre; United States of America; Theatre history